2021
DOI: 10.3389/fonc.2020.587422
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Features of Triple-Negative Breast Carcinomas Are Correlated With mRNA–lncRNA Signatures and Risk of Tumor Recurrence

Abstract: BackgroundTo determine a correlation between mRNA and lncRNA signatures, sonographic features, and risk of recurrence in triple-negative breast cancers (TNBC).MethodsWe retrospectively reviewed the data from 114 TNBC patients having undergone transcriptome analysis. The risk of tumor recurrence was determined based on the correlation between transcriptome profiles and recurrence-free survival. Ultrasound (US) features were described according to the Breast Imaging Reporting and Data System. Multivariate logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Interestingly, the positive relationship between the malignant-like sonographic features and the poor prognosis of TNBCs was contrary to our previous finding that TNBCs with benign-like sonographic features have aggressive biological properties [ 27 , 46 ] and a higher recurrence risk [ 26 ]. Some other researches also came to the controversial conclusion that TNBCs with circumscribed margins and posterior acoustic enhancement share more proliferative and aggressive biological properties.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the positive relationship between the malignant-like sonographic features and the poor prognosis of TNBCs was contrary to our previous finding that TNBCs with benign-like sonographic features have aggressive biological properties [ 27 , 46 ] and a higher recurrence risk [ 26 ]. Some other researches also came to the controversial conclusion that TNBCs with circumscribed margins and posterior acoustic enhancement share more proliferative and aggressive biological properties.…”
Section: Discussioncontrasting
confidence: 99%
“…Some other researches also came to the controversial conclusion that TNBCs with circumscribed margins and posterior acoustic enhancement share more proliferative and aggressive biological properties. Our previous study [ 26 ] and the study by Elfgen et al [ 47 ] show that although BLIS has a higher probability of presenting with benign-like sonographic features, it tends to have poorer survival outcomes than the other three subtypes of TNBC. While the two studies only identify the relationship between ultrasound characteristics and different subtypes of TNBCs, they did not analyze the association between sonographic features and disease outcomes directly.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies found that the CEUS perfusion pattern of medullary carcinoma usually presents as regular morphology, with well-defined margins and homogenous enhancement. 40 TN subtype BC has been reported 41 to have a smooth boundary, which may be related to the relatively rapid progression of the tumor. The rapid growth and internal microenvironment of the TN subtype of BC results in fast enhancement and hyperenhancement perfusion patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a retrospective study, our clinical observation of a correlation between improved outcomes and concomitant cetirizine stands for a favorable drug interaction where increased macrophage killing phenotype in the tumor microenvironment has a beneficial effect potentiating the immunotherapy. Indeed, the expression of CCL8, IFIT1, IFIT3, IFI27, MX1, and RSAD2 has previously been considered favorably prognostic in several types of cancer [4,6,8,20].…”
Section: Discussionmentioning
confidence: 99%